(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the methodological foundations of using digital technologies in visual arts education. It highlights how the integration of digital tools — such as graphic tablets, digital drawing software, 3D modeling platforms, animation technologies, and virtual reality — enhances students’ creative thinking, spatial imagination, aesthetic perception, and compositional skills. The study analyzes the differences and advantages of traditional and digital art, as well as the impact of digital environments on students’ motivation and competencies. The article provides methodological recommendations for effectively incorporating digital technologies into art education.